A lanthanium-containing iron-cobalt-nickel alloy protective coating for solid oxide fuel cell metal interconnects and a preparation method and application thereof
Patent Information
- Application Number
- CN202610902710.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-06-23
AI Technical Summary
[0013]为了克服现有技术中(Fe,Co,Ni)3O4涂层致密性不足以及Cr扩散抑制效果有限等问题,本发明的目的在于提出一种固体氧化物燃料电池金属连接体用含镧的铁钴镍合金防护涂层及其制备方法和应用,利用磁控溅射技术在铁素体不锈钢表面制备含镧的铁钴镍合金层,通过热氧化转化获得含稀土钙钛矿颗粒的(Fe,Co,Ni)3O4尖晶石防护涂层,该涂层具有三层梯度结构,能够在原子尺度有效阻挡Cr元素向外扩散,同时保持优异的高温导电性能和长期稳定性
[0032](1)本发明制备工艺简单、易于操作,采用物理气相沉积方式,工艺过程绿色环保,对环境友好。
Smart Images

Figure CN122428234B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface modification technology for key components of solid oxide fuel cells (SOFC), specifically a lanthanum-containing iron-cobalt-nickel alloy protective coating for metal interconnects of solid oxide fuel cells, its preparation method and application. Background Technology
[0002] Solid oxide fuel cells (SOFCs) are clean energy conversion devices with high energy conversion efficiency and low pollutant emissions. In SOFC stacks, metal interconnects are used to provide gas channels, connect individual cells, collect current, and separate reactant gases, making them one of the key components of the stack. Ferritic stainless steel (FSS) can form a Cr2O3 oxide film on its surface under SOFC operating conditions, exhibiting excellent oxidation resistance and high-temperature conductivity. Furthermore, it is cost-effective and its coefficient of thermal expansion matches that of other battery components, thus making it a widely used metal interconnect material.
[0003] However, during long-term service in a high-temperature oxidizing atmosphere, the Cr2O3 oxide film formed on the surface of the metal connector will continue to thicken, leading to an increase in the resistance of the connector and thus affecting the operating performance of the SOFC. At the same time, under high-temperature conditions, the Cr element in the Cr2O3 film is prone to volatilization and migration to the cathode region, causing cathode poisoning and thus reducing battery life.
[0004] To address the aforementioned issues, a highly conductive protective coating is typically applied to the surface of the metal interconnect. Common coating types include active element oxide coatings, rare earth perovskite coatings, and spinel protective coatings. (Fe,Co,Ni)3O4 spinel protective coatings have been widely studied and applied due to their excellent electrical conductivity and suitable coefficient of thermal expansion. However, when faced with the stringent commercial design life of tens of thousands of hours, microscopic thermodynamic studies have shown that a single (Fe,Co,Ni)3O4 spinel protective coating, during long-term high-temperature service, exhibits a significant decrease in the Cr content within the matrix. 3+ Ions can still slowly penetrate and migrate into the spinel lattice vacancies to the oxide film surface. Therefore, developing a composite coating structure capable of forming a barrier against the outward diffusion of chromium at the atomic scale has become a pressing technical challenge.
[0005] Rare earth perovskite materials are commonly used in the cathodes of SOFCs and the interconnects of high-temperature SOFCs, not only due to their high electrical conductivity but also because they have a coefficient of thermal expansion that matches other components. Rare earth perovskite coatings can also provide active elements to the substrate, improving its oxidation resistance. The application of rare earth perovskite coatings can reduce the oxidation rate of the substrate, improve the adhesion of the oxide film, and reduce the resistance of the interconnect. If a (Fe,Co,Ni)3O4 spinel protective coating containing rare earth perovskite can be formed on the surface of the interconnect and prepared using a dense coating method, the formed rare earth perovskite can absorb and block the diffusion of Cr, achieving a synergistic effect in improving oxidation resistance and electrical conductivity stability.
[0006] On the other hand, some existing coating preparation methods (such as screen printing and electroplating) produce coatings with high porosity and insufficient density, and usually require high-temperature sintering or cause environmental pollution problems, which are not conducive to engineering applications. In contrast, magnetron sputtering technology can prepare coatings with high purity, uniform structure and density, with controllable coating composition and good interfacial bonding strength, making it an effective method for preparing protective coatings for metal connectors.
[0007] Patent CN108390074A discloses a composite coating, its preparation method, and its application. The coating is prepared using screen printing and high-temperature sintering processes. However, the coating exhibits high porosity, insufficient density, and poor adhesion to the substrate. The rare-earth perovskite is introduced through direct mixing of powders, resulting in uneven particle distribution and weak interfacial bonding, making it impossible to form a continuous Cr diffusion barrier layer at the atomic scale. The coating structure is a single layer or a simple double layer without a gradient transition, leading to poor thermal expansion matching and easy peeling during long-term service.
[0008] Patent CN112458416A discloses a method for preparing a pentagonal high-entropy alloy spinel coating using magnetron sputtering. The method employs magnetron sputtering and thermal conversion processes to prepare the pentagonal high-entropy alloy spinel coating. However, the alloy composition is Fe-Co-Ni-Mn-Cu, and after thermal conversion, only a single spinel phase is formed, without any in-situ rare-earth perovskite particles. Its Cr-blocking effect relies solely on the lattice distortion caused by the high-entropy effect, and it cannot effectively block Cr at the atomic scale. 3+ Ions penetrate into spinel lattice vacancies.
[0009] Patent CN111146486A discloses a solid oxide fuel cell metal connector with a double-layer coating and its preparation method. The NiO / (Ni,Fe)3O4 double-layer coating is prepared using magnetron sputtering and thermal conversion processes. However, the alloy system consists of Ni and Ni-Fe, without Co and La elements, and no rare-earth perovskite phase is formed. Its Cr-blocking effect depends on the inner NiO layer, but the high-temperature conductivity of NiO is much lower than that of the spinel phase, and the double-layer structure lacks a gradient transition, resulting in a large difference in thermal expansion coefficients, which easily leads to interface cracks during long-term thermal cycling.
[0010] Patent CN103746128A discloses a double-layer coating on the surface of a metal connector for high-temperature solid oxide batteries and its preparation method. The process involves electroplating, screen printing, and multiple high-temperature sintering, resulting in a long production cycle, high energy consumption, and environmental pollution from the electroplating process. The total coating thickness reaches 30–90 μm, leading to a significant increase in interfacial resistance.
[0011] The patent with publication number CN120210753A proposes a method for preparing a manganese cobalt spinel coating for SOFC connectors and the coating itself. The Mn-Co spinel coating is prepared by high-power pulsed magnetron sputtering and thermal conversion process. However, the alloy system is Mn-Co, and after thermal conversion, only a single (Mn,Co)3O4 spinel phase is formed, without the synergistic Cr-blocking effect of rare earth perovskite.
[0012] While existing technologies have reported coatings combining spinel and rare-earth perovskite, most employ direct powder mixing followed by sintering, resulting in uneven perovskite particle distribution, poor interfacial bonding, and low coating density. There are also reports of spinel coatings prepared using magnetron sputtering, but these methods either fail to introduce rare-earth elements or achieve in-situ generation of rare-earth perovskite, leading to poor long-term Cr blocking effect and electrical conductivity stability. Therefore, it is necessary to provide a (Fe,Co,Ni)3O4 spinel protective coating containing rare-earth perovskite, which offers controllable processing, is environmentally friendly, produces a dense coating, and exhibits strong adhesion to the substrate, along with its preparation method, to overcome the aforementioned shortcomings of existing technologies. Summary of the Invention
[0013] To overcome the problems of insufficient density and limited Cr diffusion suppression effect of existing (Fe,Co,Ni)3O4 coatings, the present invention aims to propose a lanthanum-containing iron-cobalt-nickel alloy protective coating for metal interconnects of solid oxide fuel cells, its preparation method, and its application. A lanthanum-containing iron-cobalt-nickel alloy layer is prepared on the surface of ferritic stainless steel using magnetron sputtering technology. A (Fe,Co,Ni)3O4 spinel protective coating containing rare-earth perovskite particles is obtained through thermal oxidation conversion. This coating has a three-layer gradient structure, which can effectively block the outward diffusion of Cr at the atomic scale while maintaining excellent high-temperature conductivity and long-term stability.
[0014] To achieve the above objectives, the present invention provides the following technical solution:
[0015] A method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect includes the following steps:
[0016] S1 substrate pretreatment: Ferritic stainless steel with a Cr content of 16-25 mass% is selected as the substrate. The surface is polished sequentially using 240#, 400#, and 600# SiC wet sandpaper until the surface is bright. The edges and corners are then ground and chamfered. Silica abrasive is used for sandblasting, with compressed air pressure ranging from 0.2 to 0.5 MPa. The sandblasted substrate is then placed in an acetone solution and ultrasonically cleaned for 10-20 minutes before being removed and dried.
[0017] S2 Target Cleaning: Before the formal implementation of the sputtering process, the lanthanum-containing iron-cobalt-nickel alloy target is cleaned using DC magnetron sputtering in a substrate-free state to remove oxides and impurities from the target surface. When cleaning the target using DC magnetron sputtering, the sputtering time is 10-30 min, the sputtering temperature is 180-220℃, the vacuum degree is 0.1-0.15 Pa, and the current is 2.5-3.5 A.
[0018] S3 Magnetron sputtering deposition of lanthanum-containing iron-cobalt-nickel alloy layer: using lanthanum-containing iron-cobalt-nickel alloy target as cathode and ferritic stainless steel as anode, magnetron sputtering is performed in an argon atmosphere with sputtering current of 2.5–3.5 A, sputtering pressure of 0.1–0.15 Pa, sputtering temperature of 150–250 °C, and deposition time of 0.5–2.5 hours to form lanthanum-containing iron-cobalt-nickel alloy layer on substrate surface;
[0019] S4 Thermal Oxidation Conversion for Preparation of Spinel Protective Coating: The sputtered substrate is placed in a box-type resistance furnace at 650–800℃ and oxidized in air atmosphere. The heating rate is 3–5℃ / min, and after holding at that temperature for 2–10 hours, it is cooled to room temperature with the furnace. This transforms the lanthanum-containing iron-cobalt-nickel alloy layer into a (Fe,Co,Ni)3O4 spinel protective coating containing in-situ generated rare earth perovskite particles. Simultaneously, a composite gradient structure is formed on the surface of the metal connector, consisting of a thermally grown Cr2O3 layer on the substrate, a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles formed by thermal oxidation conversion of the magnetron sputtered alloy layer, and a pure (Fe,Co,Ni)3O4 layer, arranged from the inside out.
[0020] In the preparation method of the lanthanum-containing iron-cobalt-nickel alloy protective coating for the metal connector of the solid oxide fuel cell, in step S1, the ultrasonic cleaning time with acetone is 15 min and the ultrasonic power is 80-100 W.
[0021] In the preparation method of the lanthanum-containing iron-cobalt-nickel alloy protective coating for the metal connector of the solid oxide fuel cell, in step S3, the mechanical pump is first turned on to pre-evacuate to 4-6 Pa, and then the diffusion pump is turned on to finely evacuate to a vacuum degree of 5×10⁻⁶ Pa. -3 ~7×10 -3 Pa, followed by magnetron sputtering in an argon atmosphere.
[0022] In the step S3 of the preparation method of the lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect, the atomic ratio of Fe, Co, and Ni in the lanthanum-containing iron-cobalt-nickel alloy target material is Fe:Co:Ni=(1 to 2):1:(0.5 to 1), and the mass percentage of La is 2 to 5%.
[0023] In the step S3 of the preparation method of the lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect, the distance between the target material and the substrate is 6 to 10 cm, and the rotating speed of the turret is 40 to 60 r / min.
[0024] In the step S4 of the preparation method of the lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect, during the thermal oxidation conversion process, the La element preferentially reacts with the Fe element to generate LaFeO3 type nano-perovskite particles in situ, and as the substrate elements diffuse outward, the La element reacts with Cr and Mn elements to form LaMn 1-x Cr x O3 which wraps LaFeO3 inside, LaMn 1-x Cr x O3 satisfies 0<x<1, and these rare earth perovskite particles are uniformly dispersed in the (Fe,Co,Ni)3O4 spinel matrix.
[0025] A lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect, after thermal oxidation conversion, forms a composite gradient structure sequentially from inside to outside as a thermally grown Cr2O3 layer on the substrate, a (Fe,Co,Ni)3O4 spinel layer containing in-situ generated rare earth perovskite nanoparticles, and a pure (Fe,Co,Ni)3O4 layer.
[0026] For the lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect, after the protective coating is continuously operated for 10 weeks in an air atmosphere at 800°C, the area specific resistance in the temperature range of 700 to 800°C is lower than 15 mΩ•cm 2 .
[0027] For the lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect, in the composite gradient structure, the thickness of the Cr2O3 layer is 1 to 2 μm, the thickness of the (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles is 2 to 3 μm, the thickness of the pure (Fe,Co,Ni)3O4 layer is 1 to 2 μm, and the total thickness is 4.1 to 5.9 μm.
[0028] An application of the protective coating in surface protection and electrical conduction of metal interconnects for solid oxide fuel cells.
[0029] The design concept of the present invention is as follows:
[0030] In existing technologies, during long-term high-temperature service, the substrate Cr... 3+ Ions can still slowly penetrate to the coating surface, leading to cathode poisoning. Existing coating preparation processes (screen printing, electroplating, etc.) suffer from low density, poor adhesion, complex processes, and severe environmental pollution. Existing composite coatings exhibit poor thermal expansion matching, insufficient long-term conductivity stability, and excessive coating thickness leads to increased interfacial resistance. This invention uses magnetron sputtering to uniformly disperse La in the Fe-Co-Ni alloy matrix, rather than directly adding perovskite powder, ensuring uniform La distribution at the atomic scale. During air oxidation at 650–800℃, La reacts with O and Fe / Co / Ni elements to generate nanoscale rare earth perovskite particles in situ, which are uniformly dispersed in the spinel matrix, forming an atomic-level Cr diffusion barrier layer. During the thermal oxidation conversion, due to differences in element diffusion rates, La preferentially reacts with Fe to generate LaFeO3-type nanoscale perovskite particles. As the matrix elements diffuse outward, La reacts with Cr and Mn to generate LaMn. 1-x Cr x O3 encapsulates LaFeO3, and these rare-earth perovskite particles are uniformly dispersed within a (Fe,Co,Ni)3O4 spinel matrix. The surface of the metal connector forms a composite gradient structure from the inside out: a thermally grown Cr2O3 layer on the substrate, a (Fe,Co,Ni)3O4 spinel layer containing rare-earth perovskite particles formed by the thermal oxidation transformation of a magnetron sputtered alloy layer, and a pure (Fe,Co,Ni)3O4 layer. The coefficient of thermal expansion gradually transitions from the substrate to the surface, significantly reducing interfacial stress. A dense alloy layer is prepared using environmentally friendly physical vapor deposition technology, completing the coating phase transformation through a single low-temperature thermal oxidation transformation, eliminating the need for multiple high-temperature sintering processes, making the process simple and controllable.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0032] (1) The preparation process of this invention is simple and easy to operate. It adopts physical vapor deposition and the process is green and environmentally friendly.
[0033] (2) The magnetron sputtering process of this invention has high sputtering atomic energy, which is beneficial to obtaining a dense coating that is firmly bonded to the substrate. The coating composition and thickness can be precisely controlled by adjusting the target material composition and sputtering time. The one-time thermal oxidation conversion process has low energy consumption and is easy to industrialize.
[0034] (3) Compared to the (Fe,Co,Ni)3O4 spinel protective coating, the (Fe,Co,Ni)3O4 spinel protective coating containing rare earth perovskite particles exhibits superior electrical conductivity and a matching coefficient of thermal expansion at high temperatures, and can more effectively suppress the outward diffusion of Cr and the inward diffusion of O, making it suitable as a protective and conductive coating for the surface of the metal interconnect of solid oxide fuel cells. This invention introduces La through alloying, generating uniformly dispersed rare earth perovskite particles in situ during the thermal oxidation conversion process. These in-situ generated rare earth perovskite particles uniformly fill the spinel lattice vacancies, effectively blocking Cr at the atomic scale. 3+ Ions diffuse outward, significantly improving the Cr-blocking effect of the coating.
[0035] (4) In the process of thermal oxidation conversion, the present invention naturally forms a gradient structure of Cr2O3 layer (matrix oxidation), (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles (intermediate Cr barrier layer), and pure (Fe,Co,Ni)3O4 layer (outer conductive layer). The thermal expansion coefficient of the three-layer gradient structure gradually transitions from the ferritic stainless steel matrix to the pure spinel layer, which effectively reduces the interfacial stress during thermal cycling and improves the adhesion and anti-peeling ability of the coating.
[0036] (5) The total thickness of the coating of this invention is only 4.1–5.9 μm, which minimizes interface resistance and material cost while ensuring protective effect. The ASR value of the coating after 10 weeks of long-term service at 800°C is less than 15 mΩ•cm. 2 It has excellent high-temperature conductivity and long-term stability, making it suitable as a protective and conductive coating for the surface of metal interconnects in solid oxide fuel cells. Attached Figure Description
[0037] Figure 1 The image shows the cross-sectional morphology and elemental line scan of the coated metal connector in Embodiment 1 of the present invention.
[0038] Figure 2 The image shows the cross-sectional morphology and elemental line scan of the coated metal connector in Embodiment 1 of the present invention after 10 weeks in the working environment of a solid oxide fuel cell cathode.
[0039] Figure 3 The image shows the phase structure analysis (XRD) spectrum of the coated metal connector in Example 1 of this invention after 10 weeks in the working environment of a solid oxide fuel cell cathode.
[0040] Figure 4 The surface resistivity (ASR) curve of the coated metal connector in Embodiment 1 of the present invention after 10 weeks in the working environment of the cathode of a solid oxide fuel cell. Detailed Implementation
[0041] In its specific implementation, this invention proposes a lanthanum-containing iron-cobalt-nickel alloy protective coating for metal interconnects in solid oxide fuel cells, its preparation method, and its application. The preparation method includes: mechanically polishing, sandblasting, and cleaning the metal interconnect substrate; subsequently, depositing a lanthanum-containing iron-cobalt-nickel alloy layer on the substrate surface using magnetron sputtering; and finally, heat-treating the alloy layer in a high-temperature air atmosphere to transform it into a (Fe,Co,Ni)3O4 spinel protective coating containing rare earth perovskite particles.
[0042] The technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments, but the implementation of the present invention is not limited thereto.
[0043] Example 1
[0044] This embodiment provides a protective coating for a metal interconnect of a solid oxide fuel cell. The coating, from the inside out, consists of a Cr2O3 layer, a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles, and a (Fe,Co,Ni)3O4 layer. The specific steps include:
[0045] (1) Matrix treatment: The surface of ferritic stainless steel (grade SUS430) was polished sequentially with 240#, 400# and 600# SiC wet sandpaper until the surface was bright. The edges and corners were then beveled and chamfered. The sample was then sandblasted with silica abrasive particles at a compressed air pressure of 0.4 MPa. The sandblasted sample was placed in anhydrous acetone and ultrasonically cleaned for 10 min with an ultrasonic power of 90 W. The sample was then removed and air-dried.
[0046] (2) Target cleaning: In the absence of substrate, the lanthanum-containing iron-cobalt-nickel alloy target was cleaned by DC magnetron sputtering to remove surface oxides and impurities. Sputtering was performed for 10 min at a temperature of 180°C, a vacuum of 0.1 Pa, a voltage of 330 V, and a current of 2.5 A.
[0047] (3) Deposition of lanthanum-containing iron-cobalt-nickel alloy layer: A lanthanum-containing iron-cobalt-nickel alloy layer was deposited by DC magnetron sputtering. The atomic ratio of Fe, Co, and Ni was Fe:Co:Ni = 1.5:1:0.5. The target material contained 5% by mass of La, i.e., Fe 1.5 CoNi 0.5La5wt% alloy target material. The distance between the target and the substrate is 8 cm. First, turn on the mechanical pump and pre-evacuation valve, and wait until the vacuum reaches 5 Pa. Then, turn on the diffusion pump and fore-stage valve, and wait until the vacuum reaches 5 × 10 Pa. -3 Pa, then Ar gas is introduced to make the sputtering pressure in the chamber 0.1 Pa. Fe 1.5 CoNi 0.5 Using a 5wt% La alloy target as the cathode and a ferritic stainless steel substrate as the anode, the sputtering current was 2.5 A, the sample holder rotation speed was 40 r / min, the sputtering temperature was 200℃, and the sputtering deposition time was 1.5 h, resulting in a 4.1 μm thick Fe layer. 1.5 CoNi 0.5 La5wt% alloy layer.
[0048] (4) Thermal oxidation conversion: The deposited substrate is oxidized in an air atmosphere at 800℃ with a heating rate of 4℃ / min. After holding at the temperature for 5 hours, it is cooled to room temperature with the furnace to form a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles.
[0049] It should be noted that, since the working environment of the solid oxide fuel cell cathode is an air atmosphere of 650–800°C, in order to characterize the effect of the coating on the antioxidant properties of the connector and the ability to inhibit the outward migration of Cr, the oxidation tests in the embodiments of the present invention are all carried out in air at 800°C to simulate the working environment of the solid oxide fuel cell cathode.
[0050] like Figure 1 As shown in the cross-sectional morphology, the interface between the coating and the substrate is clear and straight, without obvious cracks, pores, or peeling, indicating that the alloy layer prepared by magnetron sputtering has good adhesion to the substrate. Elemental line scan analysis shows that La is uniformly distributed throughout the coating area without obvious agglomeration, proving that magnetron sputtering achieved atomic-level uniform dispersion of La in the Fe-Co-Ni alloy matrix. Co and Ni are completely distributed in the coating area, consistent with the La distribution, proving the uniform composition of the alloy layer. The magnetron sputtering process used in this invention can prepare a lanthanum-containing iron-cobalt-nickel alloy precursor layer with uniform composition, dense structure, and strong adhesion to the substrate. The uniform dispersion of La is the basis for the subsequent in-situ generation of rare earth perovskite particles.
[0051] like Figure 2As shown in the cross-sectional morphology, after thermal oxidation transformation, the structure changes from a single alloy layer to a three-layer gradient composite structure. The innermost layer (closest to the substrate) is a dense oxide layer approximately 1–2 μm thick, corresponding to the thermally grown Cr₂O₃ layer on the substrate. The middle layer is approximately 2–3 μm thick, corresponding to a (Fe,Co,Ni)₃O₄ spinel layer containing in-situ generated rare-earth perovskite particles. These in-situ generated perovskite nanoparticles are uniformly distributed at the spinel grain boundaries and lattice vacancies, physically blocking Cr₂O₃ particles. 3+ The coating utilizes ion diffusion channels and reacts with diffused elements to form a stable rare-earth perovskite phase, fixing Cr elements within the coating and preventing their volatilization to the surface. The concentration of Cr drops sharply at the rare-earth perovskite layer, demonstrating its Cr-blocking effect. The outermost layer (closest to the surface) is approximately 1–2 μm thick, corresponding to a pure (Fe,Co,Ni)3O4 spinel layer. The interfaces between layers are clear, with no obvious cracks or peeling, indicating excellent high-temperature stability and thermal cycling adaptability of the coating.
[0052] like Figure 3 As shown, the diffraction peaks marked "1" all correspond to the characteristic diffraction peaks of the (Fe,Co,Ni)3O4 spinel phase. The thermal oxidation conversion process can transform the lanthanum-containing iron-cobalt-nickel alloy layer into the (Fe,Co,Ni)3O4 spinel main phase, proving that the alloy layer has been completely transformed into a spinel structure after thermal oxidation conversion.
[0053] like Figure 4 As shown, the ASR test conditions were as follows: The four-probe method was used for testing in air atmosphere, with a test temperature range of 600–800℃. Continuous oxidation was performed for 10 weeks in air atmosphere at 800℃. Within the typical operating temperature range of SOFC (700–800℃), the ASR values were all below 15 mΩ•cm. 2 (approximately 8.5–12.7 mΩ•cm) 2 The three-layer gradient structure and in-situ generated rare earth perovskite particles of this invention can improve conductivity stability and fully meet the requirements of commercial applications for surface resistivity of metal interconnects.
[0054] Example 2
[0055] This embodiment provides a protective coating for a metal interconnect of a solid oxide fuel cell. The coating, from the inside out, consists of a Cr2O3 layer, a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles, and a (Fe,Co,Ni)3O4 layer. The specific steps include:
[0056] (1) Matrix treatment: The surface of ferritic stainless steel (Crofer 22 APU) was polished with 240#, 400# and 600# SiC wet sandpaper in sequence until the surface was bright. The edges and corners were then beveled and chamfered. The sample was then sandblasted with silica abrasive particles at a compressed air pressure of 0.3 MPa. The sandblasted sample was placed in anhydrous acetone and ultrasonically cleaned for 15 min with an ultrasonic power of 80 W. The sample was then removed and air-dried.
[0057] (2) Target cleaning: In the absence of substrate, the lanthanum-containing iron-cobalt-nickel alloy target was cleaned by DC magnetron sputtering to remove surface oxides and impurities. Sputtering time was 15 min, sputtering temperature was 200℃, vacuum degree was 0.13 Pa, voltage was 350V and current was 3 A.
[0058] (3) Deposition of lanthanum-containing iron-cobalt-nickel alloy layer: A lanthanum-containing iron-cobalt-nickel alloy layer was deposited by DC magnetron sputtering. The atomic ratio of Fe, Co, and Ni was Fe:Co:Ni = 1:1:1. The target material contained 4% La by mass, i.e., FeCoNi La4wt% alloy target material. The distance between the target material and the substrate was 8 cm. First, the mechanical pump and pre-evacuation valve were turned on. After the vacuum was evacuated to 5 Pa, the diffusion pump and fore-stage valve were turned on. After the vacuum was evacuated to 6 × 10 Pa, the diffusion pump and fore-stage valve were turned on. -3 Pa was then introduced, and Ar gas was introduced to make the sputtering pressure in the chamber 0.13 Pa. Using FeCoNiLa4wt% alloy target as cathode and ferritic stainless steel substrate as anode, sputtering current 3 A, sample holder rotation speed 50 r / min, sputtering temperature 180℃, sputtering deposition for 2 h, a 5 μm thick FeCoNiLa4wt% alloy layer was obtained.
[0059] (4) Thermal oxidation conversion: The deposited substrate is oxidized in an air atmosphere at 800℃ with a heating rate of 3℃ / min. After holding at this temperature for 6 hours, it is cooled to room temperature in the furnace to form a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles.
[0060] Example 3
[0061] This embodiment provides a protective coating for a metal interconnect of a solid oxide fuel cell. The coating, from the inside out, consists of a Cr2O3 layer, a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles, and a (Fe,Co,Ni)3O4 layer. The specific steps include:
[0062] (1) Matrix treatment: The surface of ferritic stainless steel (grade UNS S44625) was polished sequentially with 240#, 400# and 600# SiC wet sandpaper until the surface was bright. The edges and corners were then beveled and chamfered. The sample was then sandblasted with silica abrasive particles at a compressed air pressure of 0.5 MPa. The sandblasted sample was placed in anhydrous acetone and ultrasonically cleaned for 20 min at a power of 100 W. The sample was then removed and air-dried.
[0063] (2) Target cleaning: In the absence of substrate, the lanthanum-containing iron-cobalt-nickel alloy target was cleaned by DC magnetron sputtering to remove surface oxides and impurities. Sputtering time was 20 min, sputtering temperature was 220℃, vacuum degree was 0.15 Pa, voltage was 350V and current was 3.5 A.
[0064] (3) Deposition of lanthanum-containing iron-cobalt-nickel alloy layer: The lanthanum-containing iron-cobalt-nickel alloy layer was deposited by DC magnetron sputtering. The atomic ratio of Fe, Co, and Ni was Fe:Co:Ni = 2:1:0.5. The target material contained 2% by mass of La, i.e., Fe2CoNi. 0.5 La2wt% alloy target material. The distance between the target and the substrate is 8 cm. First, turn on the mechanical pump and pre-evacuation valve, and wait until the vacuum reaches 5 Pa. Then, turn on the diffusion pump and fore-stage valve, and wait until the vacuum reaches 7 × 10 Pa. -3 Pa, then Ar gas is introduced to make the sputtering pressure in the chamber 0.15 Pa. Fe2CoNi 0.5 Using a La2wt% alloy target as the cathode and a ferritic stainless steel substrate as the anode, the sputtering current was 3.5 A, the sample holder rotation speed was 60 r / min, the sputtering temperature was 160℃, and the sputtering deposition time was 2.5 h, resulting in a 5.9 μm thick Fe2CoNi sputtering layer. 0.5 La2wt% alloy layer.
[0065] (4) Thermal oxidation conversion: The deposited substrate is oxidized in an air atmosphere at 800℃ with a heating rate of 5℃ / min. After holding at the temperature for 4 hours, it is cooled to room temperature with the furnace to form a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles.
[0066] The results show that the coating prepared by this invention has a dense structure and a strong bond with the substrate, effectively inhibiting the outward diffusion of Cr and the inward diffusion of O. It exhibits good oxidation resistance and electrical conductivity, and can be used for the protection of the surface of metal interconnects in solid oxide fuel cells. After 10 weeks of continuous service in air at 800°C, the area resistivity of the protective coating is less than 15 mΩ•cm within the temperature range of 700–800°C. 2 .
Claims
1. A method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect, characterized in that, Includes the following steps: S1 substrate pretreatment: Ferritic stainless steel with a Cr content of 16-25 mass% is selected as the substrate. The surface is polished sequentially using 240#, 400#, and 600# SiC wet sandpaper until the surface is bright. The edges and corners are then ground and chamfered. Silica abrasive is used for sandblasting, with compressed air pressure ranging from 0.2 to 0.5 MPa. The sandblasted substrate is then placed in an acetone solution and ultrasonically cleaned for 10-20 minutes before being removed and dried. S2 Target Cleaning: Before the formal implementation of the sputtering process, the lanthanum-containing iron-cobalt-nickel alloy target is cleaned using DC magnetron sputtering in a substrate-free state to remove oxides and impurities from the target surface. When cleaning the target using DC magnetron sputtering, the sputtering time is 10-30 min, the sputtering temperature is 180-220℃, the vacuum degree is 0.1-0.15 Pa, and the current is 2.5-3.5 A. S3 Magnetron sputtering deposition of lanthanum-containing iron-cobalt-nickel alloy layer: using lanthanum-containing iron-cobalt-nickel alloy target as cathode and ferritic stainless steel as anode, magnetron sputtering is performed in an argon atmosphere with sputtering current of 2.5–3.5 A, sputtering pressure of 0.1–0.15 Pa, sputtering temperature of 150–250 °C, and deposition time of 0.5–2.5 hours to form lanthanum-containing iron-cobalt-nickel alloy layer on substrate surface; S4 Thermal Oxidation Conversion for Preparation of Spinel Protective Coating: The sputtered substrate is placed in a box-type resistance furnace at 650-800℃ and oxidized in air atmosphere. The heating rate is 3-5℃ / min, and after holding at the temperature for 2-10 hours, it is cooled to room temperature with the furnace. This transforms the lanthanum-containing iron-cobalt-nickel alloy layer into a (Fe,Co,Ni)3O4 spinel protective coating containing in-situ generated rare earth perovskite particles. At the same time, a composite gradient structure is formed on the surface of the metal connector, consisting of a thermally grown Cr2O3 layer on the substrate, a (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles formed by thermal oxidation conversion of the magnetron sputtered alloy layer, and a pure (Fe,Co,Ni)3O4 layer, which are arranged from the inside out. In the lanthanum-containing iron-cobalt-nickel alloy target, the atomic ratio of Fe, Co, and Ni is Fe:Co:Ni = (1~2):1:(0.5~1), and the mass percentage of La is 2~5%.
2. The method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect according to claim 1, characterized in that, In step S1, the ultrasonic cleaning time with acetone is 15 minutes, and the ultrasonic power is 80-100W.
3. The method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect according to claim 1, characterized in that, In step S3, the mechanical pump is first turned on to pre-pump to 4-6 Pa, and then the diffusion pump is turned on to finely pump to a vacuum of 5×10⁻⁶ Pa. -3 ~7×10 -3 Pa, followed by magnetron sputtering in an argon atmosphere.
4. The method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect according to claim 1, characterized in that, In step S3, the distance between the target and the substrate is 6-10 cm, and the rotation speed of the rotating frame is 40-60 r / min.
5. The method for preparing a lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect according to claim 1, characterized in that, In step S4, during the thermal oxidation conversion, La preferentially reacts with Fe to form LaFeO3-type nano-perovskite particles in situ. As the matrix elements diffuse outward, La reacts with Cr and Mn to form LaMn. 1-x Cr x O3 encapsulates LaFeO3, LaMn 1-x Cr x O3 contains 0 <x<1。 6. A lanthanum-containing iron-cobalt-nickel alloy protective coating for a solid oxide fuel cell metal interconnect prepared using the method described in any one of claims 1 to 5, characterized in that, After thermal oxidation conversion, a composite gradient structure is formed from the inside out, consisting of a Cr2O3 layer grown on the substrate, a (Fe,Co,Ni)3O4 spinel layer containing in-situ generated rare earth perovskite nanoparticles, and a pure (Fe,Co,Ni)3O4 layer.
7. The lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect according to claim 6, characterized in that, After 10 weeks of continuous service in air at 800°C, the protective coating exhibits an area resistivity of less than 15 mΩ•cm within a temperature range of 700–800°C. 2 .
8. The lanthanum-containing iron-cobalt-nickel alloy protective coating for the solid oxide fuel cell metal interconnect according to claim 6, characterized in that, In the composite gradient structure, the thickness of the Cr2O3 layer is 1–2 μm, the thickness of the (Fe,Co,Ni)3O4 spinel layer containing rare earth perovskite particles is 2–3 μm, the thickness of the pure (Fe,Co,Ni)3O4 layer is 1–2 μm, and the total thickness is 4.1–5.9 μm.
9. The application of the protective coating as described in any one of claims 6 to 8 in the surface protection and conductivity of metal interconnects in solid oxide fuel cells.
Citation Information
Patent Citations
Double-layer coating on metal connector surface of high-temperature solid oxide cell and preparation method thereof
CN103746128A
Composite coating, preparation method and application thereof
CN108390074A
Solid oxide fuel cell metal connector with double-layer coating and preparation method thereof
CN111146486A
Method for manufacturing five-element high-entropy alloy spinel coating through magnetron sputtering method
CN112458416A
Rare earth oxide-inert metal-spinel conductive composite coating and preparation method thereof
CN118480768A
